2020
DOI: 10.1186/s12889-020-09015-7
|View full text |Cite
|
Sign up to set email alerts
|

Human Toxoplasma gondii infection in Nigeria: a systematic review and meta-analysis of data published between 1960 and 2019

Abstract: Background: Over 70% of the worlds' population is infected by Toxoplasma gondii; a pathogen capable of causing cerebral toxoplasmosis in HIV patients and neonatal complications like miscarriage, chorioretinitis, hydrocephalus, cerebral calcification and foetal death in the third trimester of pregnancy. In spite of this, the burden of this zoonotic pathogen is poorly understood in Nigeria. The aim of the present study therefore, is to determine the burden of T. gondii among normal individuals, HIV patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 83 publications
1
3
2
Order By: Relevance
“…The present study revealed that the global pooled seroprevalence of chronic T. gondii infection was 38.27% (95% CI: 32.04−44.49) among neuropsychiatric patients and 25.31% (95% CI: 21.53−29.08) in apparently healthy controls with high heterogeneity ( I 2 value of 98.3%). This finding is in line with the global pooled prevalence of T. gondii among HIV patients (35.8%; 95% CI: 30.8−40.7) 76 and the national overall pooled prevalence of human T. gondii infection in Nigeria (32.92% [95% CI: 27.89−38.37]) 77 . Toxoplasma gondii induces a suite of behavioral and neurological changes in the infected individuals.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The present study revealed that the global pooled seroprevalence of chronic T. gondii infection was 38.27% (95% CI: 32.04−44.49) among neuropsychiatric patients and 25.31% (95% CI: 21.53−29.08) in apparently healthy controls with high heterogeneity ( I 2 value of 98.3%). This finding is in line with the global pooled prevalence of T. gondii among HIV patients (35.8%; 95% CI: 30.8−40.7) 76 and the national overall pooled prevalence of human T. gondii infection in Nigeria (32.92% [95% CI: 27.89−38.37]) 77 . Toxoplasma gondii induces a suite of behavioral and neurological changes in the infected individuals.…”
Section: Discussionsupporting
confidence: 87%
“…To the best of our knowledge, our review gondii infection in Nigeria (32.92% [95% CI: 27.89−38.37]). 77 Toxoplasma gondii induces a suite of behavioral and neurological changes in the infected individuals. There are pronounced behavioral changes in the individual infected with T. gondii.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the present finding is higher than the global pooled prevalence estimates in pregnant women (1.1% to 33.8%) [11,13] and HIV infected individuals (3.24% to 44.2%) [1,5,14]. Significantly lower pooled seroprevalence reports in pregnant women and HIV/AIDS patients were also reported in Mexico (15.62% & 20.2%) [54], Iran (41% & 50.1%) [55,56] and Nigeria (40.3% & 31.7%) [57]. This variation might be attributable to the difference in local climatic situations which determine the survival of oocysts and favours the dissemination and sporulation of oocysts, nutritional habit, the status of public health and sanitary services, personal hygiene, sources of drinking water, socio-cultural differences, residence, stray or pet cat density and management, and levels of close contact with cats [1,7,13,17,[58][59][60].…”
Section: The Pooled Prevalence Of Seropositivity For Toxoplasma Gondicontrasting
confidence: 70%
“…Toxoplasma gondii is an intracellular parasite that can infect most warm-blooded animals, where it may invade the central nervous system and provoke neuroinflammation and behavioral changes (for recent reviews, see Mendez and Koshy, 2017 ; Martinez et al., 2018 ; Chen et al., 2019 ; de Haan et al., 2021 ; Nasuhidehnavi and Yap, 2021 ; Nayeri et al., 2021 ; Postolache et al., 2021 ). It is estimated that approximately 30% of the world’s population is infected with this protozoan, but there is much greater prevalence in African and South American countries ( Agordzo et al., 2019 ; Karshima and Karshima, 2020 ; Rahmanian et al., 2020 ; de Lima Bessa et al., 2021 ). For example, in Brazil seroprevalence is 92%, but in the USA, it is only 22.5% ( Jones et al., 2001 ; Jones and Dubey, 2014 ).…”
Section: Introductionmentioning
confidence: 99%